Molecular Modeling for Nanomaterial–Biology Interactions: Opportunities, Challenges, and Perspectives - Casalini, Tommaso; Limongelli, Vittorio; Schmutz, Mélanie; Som, Claudia; Jordan, Olivier; Wick, Peter; Borchard, Gerrit; Perale, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2019)
The injection of nanoparticles (NP) into blood stream leads to the formation of a so-called “nano–bio” interface, where dynamic interactions between nanoparticles surface and blood components take place. A common consequence is the formation of protein corona, that is, a network of adsorbed proteins that can strongly alter surface properties of the nanoparticle. Protein corona and the resulting structural changes experienced by adsorbed proteins can lead to substantial deviations from the expected cellular uptake as well as biological responses, such as NP aggregation and NP-induced protein fibrillation, NP interference with enzymatic activity or the exposure of new antigenic epitopes. A detailed understanding of the nano–bio interface is still challenging, due to synergistic effects of several influencing factors like pH, ionic strength and hydrophobic effects, just to name a few. Because of the multiscale complexity of the system, modeling approaches at molecular level represent the ideal choice for a detailed understanding of the driving forces and in particular the early events of the nano–bio interface. This review aims at exploring and discussing the opportunities and perspectives offered by molecular modeling in this field, through selected examples from literature.